1H‐NMR‐based water‐soluble low molecular weight compound characterization and fatty acid composition of boiled Wuding chicken during processing. (21st August 2018) - Xiao, Zhichao; Luo, Yuting; Wang, Guiying; Ge, Changrong; Zhou, Guanghong; Zhang, Wangang; Liao, Guozhou
Abstract: BACKGROUND: Boiled Wuding chicken was produced using whole chicken by washing, boiling 1 h with salt, deep frying, and boiling 2 h. The effect of the process on the water‐soluble low molecular weight (WLOM) compound profiles of products was characterized using proton nuclear magnetic resonance spectroscopy, and the fatty acid composition of products was analyzed using gas chromatography–mass spectrometry. RESULTS: The metabolome was dominated by 49 WLOM compounds, and 22 fatty acid compounds were detected. Principal component (PC)1 and PC2 explained a total of 93.4% and 3% of variance respectively. Compared with the control group, the total WLOM compound and fatty acid contents of the chicken breast were significantly decreased in the other three processing stages ( P  < 0.05). Comprehensive multivariate data analysis showed significant differences about precursor substance between the different processing including creatine, lactate, creatinine, glucose, taurine, anserine, and acetate ( P  < 0.05). CONCLUSION: These results contribute to a more accurate understanding of precursor substance changes of flavor in chicken meat during processing. Boiled, treated chicken had significant effects on fatty acid and WLOM compounds. © 2018 Society of Chemical Industry